Changes in Cortical Microvasculature during Misery Perfusion Measured by Two-Photon Laser Scanning Microscopy. Issue 8 (August 2014) - Tajima, Yosuke; Takuwa, Hiroyuki; Kokuryo, Daisuke; Kawaguchi, Hiroshi; Seki, Chie; Masamoto, Kazuto; Ikoma, Yoko; Taniguchi, Junko; Aoki, Ichio; Tomita, Yutaka; Suzuki, Norihiro; Kanno, Iwao; et al.
This study aimed to examine the cortical microvessel diameter response to hypercapnia in misery perfusion using two-photon laser scanning microscopy (TPLSM). We evaluated whether the vascular response to hypercapnia could represent the cerebrovascular reserve. Cerebral blood flow (CBF) during normocapnia and hypercapnia was measured by laser-Doppler flowmetry through cranial windows in awake C57/BL6 mice before and at 1, 7, 14, and 28 days after unilateral common carotid artery occlusion (UCCAO). Diameters of the cortical microvessels during normocapnia and hypercapnia were also measured by TPLSM. Cerebral blood flow and the vascular response to hypercapnia were decreased after UCCAO. Before UCCAO, vasodilation during hypercapnia was found primarily in arterioles (22.9% ± 3.5%). At 14 days after UCCAO, arterioles, capillaries, and venules were autoregulatorily dilated by 79.5% ± 19.7%, 57.2% ±32.3%, and 32.0% ± 10.8%, respectively. At the same time, the diameter response to hypercapnia in arterioles was significantly decreased to 1.9% ± 1.5%. A significant negative correlation was observed between autoregulatory vasodilation and the diameter response to hypercapnia in arterioles. Our findings indicate that arterioles play main roles in both autoregulatory vasodilation and hypercapnic vasodilation, and that the vascular response to hypercapnia can be used to estimate the cerebrovascular reserve.